2019
DOI: 10.24057/2071-9388-2019-43
|View full text |Cite
|
Sign up to set email alerts
|

Ice ridges in landfast ice of Shokal'skogo Strait

Abstract: Three first-year ice ridges have been examined with respect to geometry and morphology in landfast ice of Shokal'skogo Strait (Severnaya Zemlya Archipelago) in May 2018. Two of the studied ice ridges were located on the edge of the ridged field and were part of it, because their keels extended for a long distance deep into this field. Ice ridges characteristics are discussed in the paper. These studies were conducted using hot water thermal drilling with computer recording of the penetration rate. Boreholes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…First, our model does not account for the high macroporosity of unconsolidated FYI ridge keels, which leads to an underestimation of the thickness. Numerous studies have shown that mean ridge porosities amount to 11 %-22 % (Kharitonov and Borodkin, 2020;Kharitonov, 2019a, b;Strub-Klein and Sudom, 2012), with the largest range between 11 % and 45 % for old FYI ridges and newly formed FYI ridges, respectively (Ervik et al, 2018;Høyland, 2007). If we assume that the fraction of 86 % of deformed ice in all observations had a porosity of 11 %-22 %, the mean modeled thickness will increase by 0.1-0.3 m, to 1.8-2 m. In the context of porosity, we also discuss the uncertainties in the EM ice thickness measurements.…”
Section: Modeled Vs Observed Thickness -Limitations Of the Modelmentioning
confidence: 99%
“…First, our model does not account for the high macroporosity of unconsolidated FYI ridge keels, which leads to an underestimation of the thickness. Numerous studies have shown that mean ridge porosities amount to 11 %-22 % (Kharitonov and Borodkin, 2020;Kharitonov, 2019a, b;Strub-Klein and Sudom, 2012), with the largest range between 11 % and 45 % for old FYI ridges and newly formed FYI ridges, respectively (Ervik et al, 2018;Høyland, 2007). If we assume that the fraction of 86 % of deformed ice in all observations had a porosity of 11 %-22 %, the mean modeled thickness will increase by 0.1-0.3 m, to 1.8-2 m. In the context of porosity, we also discuss the uncertainties in the EM ice thickness measurements.…”
Section: Modeled Vs Observed Thickness -Limitations Of the Modelmentioning
confidence: 99%